Changes in body fatness affect cardiovascular outcomes more than changes in physical activity - Cayres, Suziane U. [UNESP]; Kemper, Han C. G.; Vanderlei, Luiz C. M. [UNESP]; Casonatto, Juliano; MacHado-Rodrigues, Aristides M.; Barbosa, Maurício F.; Fernandes, Rômulo A. [UNESP] (Cambridge University Press (CUP), 2017)
Objective The aim of this study was to analyse whether changes in physical activity and body fatness are related to modifications in cardiovascular risk factors among adolescents. Material and methods A sample of 89 healthy adolescents was recruited for this study. We assessed habitual physical activity, body fat percentage, arterial thickness, blood sample, and biological maturation. Multivariate models were used to analyse the relationships between independent and dependent variables. Results Physical activity (mean difference: 429.4 steps [95% confidence interval=-427 to 1286]) and body fatness (mean difference: -0.7% [95% confidence interval=-1.6-0.2]) remained stable during the study period. Independent of changes in physical activity, for each percentage increase in body fatness, femoral intima-media thickness increased by 0.007 mm (β=0.007 [95% confidence interval=0.001-0.013]). Longitudinal relationships were found for high-density lipoprotein-cholesterol (β=-0.477 mg/dl [95% confidence interval=-0.805 to -0.149]) and triacylglycerol (β=2.329 mg/dl [95% confidence interval=0.275-4.384]). Conclusion Changes in body fatness are more important than the amount of physical activity on cardiovascular and metabolic risks.
Keywords: adiposity; Adolescent; atherosclerosis; dyslipidaemias; physical activity